Hybrid Business Models as a Response to the Modern Global Challenges - Sych, Olga; Pasinovych, Iryna (Science and Innovation, 2021)
Introduction. In response to global challenges, there are emerging alternative solutions that can be based on hybrid approaches, including hybrid business models that have the characteristics of private business and the public sector in their conventional perception. Problem Statement. The discussion on the introduction and spread of hybrid forms of business, their benefits is at the early stages of development, it focuses on the motives of commercial companies to start activities traditionally performed by government or non-profit organizations. Purpose. The identification of patterns, the determination of motives for the creation and the formation of hyb rid business models. Materials and Methods. The legal framework and R&D works of researchers have been studied with the use of general scientific and special methods: analysis and synthesis for studying the current state and development of hybrid forms of business, abstraction approach, and logical method for drawing the conclusions. Results. Modern business refocuses on solving social problems. There are hybrid business models that combine the characteristics of economic entities from different sectors: public (social and environmental problems) and private (profit). The hybrid business models are represented by Benefit Corporations and B-Corporations, in which the social component is reflected in the mission, registered in the statutory documents, and is a part of the operating activities. The hybrid approach to the functioning of corporations may be deemed a continuation of the concept of corporate social responsibility as well as a way to systematic implementation of social and environment practices. Conclusions. The analyzed world experience of the development of hybrid business models should be implemented in domestic practice. It is time to widely popularize the idea and capabilities of Benefit Corporation and B-Corporation as well as to introduce legal regulation for these companies. This contributes to the most effective solution of social problems of the modern society in general and Ukraine in particular.